The Role of Quinine-Responsive Taste Receptor Family 2 in Airway Immune Defense and Chronic Rhinosinusitis - Workman, Alan D.; Maina, Ivy W.; Brooks, Steven G.; Kohanski, Michael A.; Cowart, Beverly J.; Mansfield, Corrine; Kennedy, David W.; Palmer, James N.; Adappa, Nithin D.; Reed, Danielle R.; Lee, Robert J.; Cohen, Noam A. (Frontiers in Immunology, 2018)
Background: Bitter (T2R) and sweet (T1R) taste receptors in the airway are important in innate immune defense, and variations in taste receptor functionality in one T2R (T2R38) correlate with disease status and disease severity in chronic rhinosinusitis (CRS). Quinine is a bitter compound that is an agonist for several T2Rs also expressed on sinonasal cells, but not for T2R38. Because of this property, quinine may stimulate innate immune defense mechanisms in the airway, and functional differences in quinine perception may be reflective of disease status in CRS. Methods: Demographic and taste intensity data were collected prospectively from CRS patients and non-CRS control subjects. Sinonasal tissue from patients undergoing rhinologic surgery was also collected and grown at an air-liquid interface (ALI). Nitric oxide (NO) production and dynamic regulation of ciliary beat frequency in response to quinine stimulation were assessed in vitro. Results: Quinine reliably increased ciliary beat frequency and NO production in ALI cultures in a manner consistent with T2R activation (p<0.01). Quinine taste intensity rating was performed in 328 CRS patients and 287 control subjects demonstrating that CRS with nasal polyps (CRSwNP) patients rated quinine as significantly less intense than did control subjects. Conclusions: Quinine stimulates airway innate immune defenses by increasing ciliary beat frequency and stimulating NO production in a manner fitting with T2R activation. Patient variability in quinine sensitivity is observed in taste intensity ratings, and gustatory quinine “insensitivity” is associated with CRSwNP status. Thus, taste tests for quinine may be a biomarker for CRSwNP and topical quinine has therapeutic potential as a stimulant of innate defenses.